Plasma protein binding, metabolism, reaction phenotyping and toxicokinetic studies of fenarimol after oral and intravenous administration in rats. (2nd January 2021) - Karsauliya, Kajal; Sonker, Ashish Kumar; Bhateria, Manisha; Taneja, Isha; Srivastava, Anshuman; Sharma, Manu; Singh, Sheelendra Pratap
Abstract: Fenarimol (FNL), an organic chlorinated fungicide, is widely used in agriculture for protection from fungal spores and fungi. Despite being an endocrine disruptor, no toxicokinetic data is reported for this fungicide. In the present work, we determined the plasma protein binding, metabolic pathways and toxicokinetics of FNL in rats. In vitro binding of FNL to rat and human plasma proteins was ∼90%, suggesting that FNL is a highly protein bound fungicide. The predicted in vivo hepatic clearance of FNL in rats and humans was estimated to be 36.71 and 14.39 mL/min/kg, respectively, indicating it to be an intermediate clearance compound. Reaction phenotyping assay showed that CYP3A4 mainly contributed to the overall metabolism of FNL. The oral toxicokinetic study of FNL in rats at no observed adverse effect level dose (1 mg/kg) showed maximum plasma concentration ( C max ) of 33.97 ± 4.45 ng/mL at 1 h ( T max ). The AUC0–∞ obtained was 180.18 ± 17.76 h*ng/mL, whereas, the t 1/2 was ∼4.74 h. Following intravenous administration, FNL displayed a clearance of 42.48 mL/min/kg which was close to the predicted in vivo hepatic clearance. The absolute oral bioavailability of FNL at 1 mg/kg dose in rats was 45.25%. FNL at 10 mg/kg oral dose exhibited non-linear toxicokinetics with greater than dose-proportional increase in the systemic exposure (AUC0–∞ 8270.53 ± 1798.59 h*ng/mL).